Bentuk Kerjasama Kompas TV Dan RBTV Dalam Pelaksanaan Sistem Stasiun Jaringan (SSJ) - Utami, Citra Dewi; Oktaviani, Danissa Dyah (Capture : Jurnal Seni Media Rekam, 2015)
Sistem Stasiun Jaringan (SSJ) is a broadcasting system in the world that is now being intensively carried out in Indonesia. The entire private television stations in Indonesia are required to switch to using SSJ and left the broadcasting system centralization. The focus of this study aims to investigate the implementation of the SSJ in Indonesia which is first implemented by Kompas TV with one member of the affiliation network, RBTV (Reksa Birama TV). Cooperation agreement between Kompas TV and RBTV appears differently with another cooperation model in the Kompas TV network.The approach of the research used qualitative descriptive, and the data collection used: (1) direct observation, (2) interview, (3) document review, and (4) literature. The result of research showed that cooperation of Kompas TV and RBTV formed a cartel which contained six points of cooperation, namely (1) Empowerment of human resources together, (2) Production of a joint program, (3) broadcasting program, and (4) development of shared infrastructure (5) the use of shared equipment, and (6) cooperation arrangements in the contract within a certain time.Keywords: SSJ, Kompas TV, RBTV, and cartel